Exposure to Stress or an Enriched Environment in Youth Modulates Prenatal Inflammation-Induced Cognitive Deficits in Mice and Is Associated with Hippocampal SNAP-25 Expression Levels - Wu, Yong-Fang; Cao, Lei; Zeng, Li-Ping; Zhang, Yu-Xin; Chen, Gui-Hai (Current Molecular Medicine, 2025)
<span class=
Keywords: stress